Massive Open Online Courses: Management of Facilities and Infrastructure of Arabic Learning in Digital Era - Rohmatun Lukluk Isnaini (UIN Raden Mas Said Surakarta, 2022)
Arabic learning still seems traditional and not updated. For this reason, it is necessary to adjust the times in this digital era to the demands and needs of students. This research was conducted to provide an overview of Arabic learning innovations in the digital era of Massive Open Online Courses (MOOC) and to analyze the management of facilities and infrastructure needed to support successful learning. Through a comprehensive research review, this research is intended to present the results of an analysis of the management of facilities and infrastructure in learning Arabic through MOOC in the current digital era. Data collection techniques are carried out by documentation studies or literature searches. The findings are presented systematically which are categorized into four things, namely 1) management of learning facilities and infrastructure, 2) trends in Arabic learning in the digital era, 3) MOOC in Arabic learning, and 4) management of facilities and infrastructure in language learning. Arabic via MOOC. This research contributes to providing concrete descriptions and answers to the demands of the times in the digital era in updating the implementation of Arabic learning.